The Effect of Organizational Justice on Affective Commitment with Knowledge Sharing as a Mediation Variable - Warsono, Diedy; Rahmat, Adi; Seswandi, Agus (Lembaga Riset dan Inovasi Al-Matani, 2024)
This study aims to investigate the effect of organizational justice on employee affective commitment at the Indragiri Hilir Regency Education Office, with knowledge sharing as a mediating variable. Organizational justice consists of three main dimensions: distributive, procedural, and interactional justice, which are believed to influence employee affective commitment. The method used is a survey with data collection through questionnaires distributed to employees. The results of the study indicate that organizational justice has a positive effect on affective commitment, and knowledge sharing mediates the relationship. These findings indicate that in order to increase employee affective commitment, there needs to be more effort in creating fairness in the workplace and encouraging knowledge sharing activities among employees. This study provides useful insights for leaders of the Education Office in designing policies that can increase employee affective commitment and strengthen the culture of knowledge sharing in the organizational environment.